071 Identifying the challenges to implementing a netball neuromuscular warm-up using concept mapping. (3rd March 2020) - Smyth, Erin; Appaneal, Renee; Drew, Michael; Antcliff, Alanna; Waddington, Gordon; Weissensteiner, Juanita; Newman, Phillip; Donaldson, Alex
Abstract : Background: Netball Australia is Australia's governing netball body, and introduced the 'Knee injury prevention for Netballers and Enhance performance and Extend play' (KNEE) program in 2015. Ankle sprains and ACL rupture are the most frequent and costly injuries in 17U & 19U athletes competing at the Australian Netball Championships (ANC). Thirty-eight percent of teams competing at the 2019 ANC's were not completing the KNEE program as frequently as recommended. Objective: To identify the challenges for implementing the KNEE program. Design: A mixed-methods approach for qualitative data collection and quantitative data analysis. Setting: Participants own environment. Patients (or Participants): Thirty-nine netball coaches (n=17), strength & conditioning coaches (n=5) and physiotherapists (n=16) working with 17U & 19U teams attending the 2019 ANC's. Interventions (or assessment of risk factors): The process of Concept Mapping was followed to capture challenges to implementing the KNEE program with State 17U & 19U teams. Main outcome measurements: Statements were consolidated to clusters (concepts). The importance and difficulty to overcome each challenge was rated by all participants. Results: Forty-six challenges were generated and organised into eight clusters. Statement 3 ('Making sure athletes are committed to executing the KNEE program with correct technique' ) received the highest mean importance rating (4.43 out of 5). Statement 43 ('Education is presented to coaches and S&C regarding the KNEE program but physio is only covered 2 hours/week to cover both 17s and 19s training. Never get to see whether it's implemented or how well' ) received the highest mean difficulty rating (3.11). Nineteen challenges were identified as being the most important and difficult to overcome. Conclusions: This CM process has identified 19 important and difficult challenges to overcome when implementing the Netball Australia KNEE program in 17U and 19U State teams. It is recommended that an advisory group consisting of athletes, coaches, support staff, administrators and implementation specialists is formed to address some of these KNEE implementation challenges.